2005
DOI: 10.1111/j.1468-0092.2005.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

The First Lake‐dwellers of Lithuania: Late Bronze Age Pile Settlements on Lake Luokesas

Abstract: Lake Luokesas in Lithuania has become the centre of attention in northern European wetland archaeological research after the discovery of two Late Bronze Age/Early Iron Age pile dwellings. Their unique location, chronology and building techniques have the potential to revolutionise our understanding of important aspects of wetland communities in later prehistoric Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Pottery of similar technological and stylistic traits is also known in the Lake Luokesa area not far from the Žalioji-type pottery distribution area in NE Lithuania. Two pile dwelling sites there were dated tõ 800-400 cal BC (Menotti et al 2005).…”
Section: Results and Discussion: Chronology Of Pottery Stylesmentioning
confidence: 99%
“…Pottery of similar technological and stylistic traits is also known in the Lake Luokesa area not far from the Žalioji-type pottery distribution area in NE Lithuania. Two pile dwelling sites there were dated tõ 800-400 cal BC (Menotti et al 2005).…”
Section: Results and Discussion: Chronology Of Pottery Stylesmentioning
confidence: 99%
“…The area was settled only after a hard, accessible surface was formed due to desiccation, and not over open water (suggested by Lewis 2007;Menotti et al 2005). This is indicated by the sharp transition between the dense lake marl and the organic layers.…”
Section: Cultural Layersmentioning
confidence: 99%
“…During the Neolithic and Bronze Age in Central Europe and in the Baltic area even until the Iron Age, people settled on lake shores and built up agricultural and pastoral communities there. Some researchers have shown that platforms were exposed due to fluctuations of the lake water levels during periods of low levels (Magny 2004;Menotti et al 2005). The unique aspect of lakeside settlements is that a large part of the material brought into the littoral zone by peoples and their domestic animals is well-preserved (Menotti 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations